A multicenter clinical epidemiology of pediatric pneumococcal meningitis in China: results from the Chinese Pediatric Bacterial Meningitis Surveillance (CPBMS) 2019–2020 - Wang, Caiyun; Xu, Hongmei; Liu, Gang; Liu, Jing; Yu, Hui; Chen, Biquan; Zheng, Guo; Shu, Min; Du, Lijun; Xu, Zhiwei; Huang, Lisu; Li, Haibo; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Objective To analyze the clinical epidemiological characteristics including clinical features, disease prognosis of pneumococcal meningitis (PM), and drug sensitivity of S. pneumoniae isolates in Chinese children. Methods A retrospective analysis was performed on the clinical, laboratory microbiological data of 160 hospitalized children less than 15 years of age with PM from January 2019 to December 2020 in 33 tertiary hospitals in China. Results A total of 160 PM patients were diagnosed, including 103 males and 57 females The onset age was 15 days to 15 years old, and the median age was 1 year and 3 months. There were 137 cases (85.6%) in the 3 months to <5 years age group, especially in the 3 months to <3 years age group (109 cases, 68.2%); S. pneumoniae was isolated from cerebrospinal fluid (CSF) culture in 95(35.6%), and 57(35.6%) in blood culture. The positive rates of S. pneumoniae detection by CSF metagenomic next-generation sequencing (mNGS)and antigen detection method were 40.2% (35/87) and 26.9% (21/78). Fifty-five cases (34.4%) had one or more predisposing factors of bacterial meningitis; and 113 cases (70.6%) had one or more extracranial infection diseases Fever (147, 91.9%) was the most common clinical symptom, followed by vomiting (61, 38.1%) and altered mental status (47,29.4%). Among 160 children with PM, the main intracranial imaging complications were subdural effusion and (or) empyema in 43 cases (26.9%), hydrocephalus in 24 cases (15.0%), cerebral abscess in 23 cases (14.4%), intracranial hemorrhage in 8 cases (5.0%), and other cerebrovascular diseases in 13 cases (8.1%) including encephalomalacia, cerebral infarction, and encephalatrophy. Subdural effusion and (or) empyema and hydrocephalus mainly occurred in children < 1 years old (90.7% (39/43) and 83.3% (20/24), respectively). 17 cases with PM (39.5%) had more than one intracranial imaging abnormality. S. pneumoniae isolates were completely sensitive to vancomycin (100.0%, 75/75), linezolid (100.0%,56/56), ertapenem (6/6); highly sensitive to levofloxacin (81.5%, 22/27), moxifloxacin (14/17), rifampicin (96.2%, 25/26), and chloramphenicol (91.3%, 21/23); moderately sensitive to cefotaxime (56.1%, 23/41), meropenem (51.1%, 23/45) and ceftriaxone (63.5, 33/52); less sensitive to penicillin (19.6%, 27/138) and clindamycin (1/19); completely resistant to erythromycin (100.0%, 31/31). The cure and improvement rate were 22.5% (36/160)and 66.3% (106/160), respectively. 18 cases (11.3%) had an adverse outcome, including 6 cases withdrawing treatment therapy, 5 cases unhealed, 5 cases died, and 2 recurrences. S. pneumoniae was completely susceptible to vancomycin (100.0%, 75/75), linezolid (100.0%, 56/56), and ertapenem (6/6); susceptible to cefotaxime, meropenem, and ceftriaxone in the order of 56.1% (23/41), 51.1% (23/45), and 63.5 (33/52); completely resistant to erythromycin (100.0%, 31/31). Conclusion Pediatric PM is more common in children aged 3 months to < 3 years old. Intracranial complications mostly occur in children < 1 year of age with fever being the most common clinical manifestations and subdural effusion and (or) empyema and hydrocephalus being the most common complications, respectively. CSF non-culture methods can facilitate improving the detection rate of pathogenic bacteria. More than 10% of PM children had adverse outcomes. S. pneumoniae strains are susceptible to vancomycin, linezolid, ertapenem, levofloxacin, moxifloxacin, rifampicin, and chloramphenicol.